2002
DOI: 10.1146/annurev.ento.47.091201.145234
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and Genetics of Insect Resistance to Bacillus thuringiensis

Abstract: Bacillus thuringiensis (Bt) is a valuable source of insecticidal proteins for use in conventional sprayable formulations and in transgenic crops, and it is the most promising alternative to synthetic insecticides. However, evolution of resistance in insect populations is a serious threat to this technology. So far, only one insect species has evolved significant levels of resistance in the field, but laboratory selection experiments have shown the high potential of other species to evolve resistance against Bt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
553
3
18

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(586 citation statements)
references
References 128 publications
12
553
3
18
Order By: Relevance
“…Although no study was conducted to clarify the mechanisms of resistance to Cry1F protein of S. frugiperda, the midgut binding site (including cadherin, alkaline phosphatase and aminopeptidases N) modification to Cry proteins were the most probable mechanism (Ferré and Van Rie 2002, Jurat-Fuentes et al 2011, Tiewsiri and Wang 2011 that would not substantially alter the other characters of the resistant strain. Our previous studies had shown that Cry1F-resistant S. frugiperda were not affected by Cry1F when they fed on Cry1F maize, even though they contained a high dose of bioactive Cry1F protein (Tian et al 2012(Tian et al , 2013.…”
Section: Parametersmentioning
confidence: 99%
“…Although no study was conducted to clarify the mechanisms of resistance to Cry1F protein of S. frugiperda, the midgut binding site (including cadherin, alkaline phosphatase and aminopeptidases N) modification to Cry proteins were the most probable mechanism (Ferré and Van Rie 2002, Jurat-Fuentes et al 2011, Tiewsiri and Wang 2011 that would not substantially alter the other characters of the resistant strain. Our previous studies had shown that Cry1F-resistant S. frugiperda were not affected by Cry1F when they fed on Cry1F maize, even though they contained a high dose of bioactive Cry1F protein (Tian et al 2012(Tian et al , 2013.…”
Section: Parametersmentioning
confidence: 99%
“…Entretanto, apesar das vantagens, atualmente há grande preocupação com o uso generalizado de culturas Bt, uma vez que elas podem acelerar a seleção de organismos resistentes (Zhang et al, 2013), quando estratégias de manejo adequadas, como adoção de áreas de refúgio, não são utilizadas. O surgimento da resistência pode estar relacionado à ligação das proteínas inseticidas a receptores no intestino médio das lagartas (Ferré & Van Rie, 2002). Alternativas para retardar a evolução da resistência têm sido bastante estudadas e misturas de toxinas têm sido consideradas mais eficazes se utilizadas antes da evolução da resistência, mesmo sob pressão de seleção contínua (Xue et al, 2005;Bergamasco et al, 2013).…”
Section: Introductionunclassified
“…In developing these markers an understanding of how resistance to the Bt toxins arises is paramount. In the majority of Cry-resistant insect species investigated, resistance has been linked to an alteration in the binding of Bt toxins to midgut epithelia, often correlated with reduced expression of a protein ligand (reviewed by Ferré and Van Rie, 2002). In H. armigera, Cry1Ac resistance was linked to an alteration in Cry1Ac binding to a cadherin-like protein (Akhurst et al, 2003;Xu and Wu, 2008).…”
Section: Introductionmentioning
confidence: 99%